KESIAPAN RUMAH SAKIT UMUM DAERAH SLEMAN MENGHADAPI DITETAPKANNYA PERATURAN MENTERI KESEHATAN 02.02 TAHUN 2010 TENTANG KEWAJIBAN MENGGUNAKAN OBAT GENERIK DI FASILITAS PELAYANAN KESEHATAN PEMERINTAH - , Asep Saepulloh ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Medicines are the biggest component of plan use hospital term that they may reach 70 % of all health cost. In January 14th 2010 The ministry of health issued the regulation (02.02, 2010) concerning the obligation to use generic drugs in public health service facilities. Sleman district hospital is a public health service facilities so it had the obligation to apply the regulation. Objective: These research aimed to knowing the preparedness of Sleman District Hospital in applying the regulation (02.02, 2010) concerning the obligation to use generic drugs in public health service facilities. Methods: The research employed a descriptive analytic qualitative approach. Data were taken retrospectively, collected by in-depth interview, and observation of documents in Sleman District Hospital. Results: The political will was ready, hospital regulation for applying the regulation from ministry of health was not yet prepared budgeting and financing were ready, drug choosing was prepared, drug supply was ready, drug storage was not yet prepared, management system wasn't yet prepared, generic drugs monitoring and information management were not yet ready. Conclusion: Sleman district hospital was not yet ready to apply the Ministry of Health's regulation (02.02, 2010) because some components were not yet prepared. the actual need reaffirmed political will of the stakeholders, need to be made Director SK to follow up Ministry of Healthâs (02.02, 2010) as a reference in policy implementation in the field, Internal monitoring task-force may be needed to monitor the supply of generic drugs. The training for generic drugs prescribing should also be carried out by the government or the district government and also related professional organization, especially Indonesian Medical Association (Ikatan Dokter Indonesia, IDI). Also need to set the award for the stakeholders who already prescribe generic drugs.